# SOLUTION: calculate the first derivatives f(x) for each of the following: show all work A)f(x)= 2/3x3/4 + 3/4x2/3+ 5/6x2/3 B) f(x)= 2/5x3/2 + 5/6x3/4 + 5/6x3/2 C) f(x)= 3/4x2/3 +5

Algebra ->  Algebra  -> Test -> SOLUTION: calculate the first derivatives f(x) for each of the following: show all work A)f(x)= 2/3x3/4 + 3/4x2/3+ 5/6x2/3 B) f(x)= 2/5x3/2 + 5/6x3/4 + 5/6x3/2 C) f(x)= 3/4x2/3 +5      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Test Calculators and Practice Answers archive Word Problems Lessons In Depth

 Click here to see ALL problems on test Question 63931: calculate the first derivatives f(x) for each of the following: show all work A)f(x)= 2/3x3/4 + 3/4x2/3+ 5/6x2/3 B) f(x)= 2/5x3/2 + 5/6x3/4 + 5/6x3/2 C) f(x)= 3/4x2/3 +5/6x3/2 + 3/4x3/2 Found 2 solutions by algebrapro18, funmath:Answer by algebrapro18(206)   (Show Source): You can put this solution on YOUR website!A)f(x)= 2/3x^(3/4) + 3/4x^(2/3)+ 5/6x^(2/3) B) f(x)= 2/5x^(3/2) + 5/6x^(3/4) + 5/6x^(3/2) C) f(x)= 3/4x^(2/3) +5/6x^(3/2) + 3/4x^(3/2) A) f'(x) = (2/3 * 3/4)x^(-1/4) + (3/4 * 2/3)x^(-1/3) + (5/6 * 2/3)x^(-1/3) = x^(-1/4)/2 + x^(-1/3)/2 + 5x^(1/3)/9 = 1/(2x^(1/4)) + 1/(2x^(1/3)) + 5/(9x^(1/3)) B) f'(x) = (2/5 * 3/2)x^(1/2) + (5/6 * 3/4)x^(-1/4) + (5/6 * 3/2)x^(1/2) = 3x^(1/2)/5 + 5x^(-1/4)/8 + 5x^(1/2) = 3x^(1/2)/5 + 5/(8x^(1/4)) + 5x^(1/2) C) f'(x) = (3/4 * 2/3)x^(-1/3) + (5/6 * 3/2)x^(1/2) + (3/4 * 3/2)x^(1/2) = x^(-1/3)/2 + 5x^(1/2)/4 + 9x^(1/2)/8 = 1/(2x^(1/3)) + 5x^(1/2)/4 + 9x^(1/2)/8 Answer by funmath(2925)   (Show Source): You can put this solution on YOUR website!I am assuming that the fractions after the variables are exponents, let me know if I'm not interpretting you correctly: calculate the first derivatives f(x) for each of the following: show all work A)f(x)= 2/3x3/4 + 3/4x2/3+ 5/6x2/3 f'(x)= f'(x)= f'(x)= : B) f(x)= 2/5x3/2 + 5/6x3/4 + 5/6x3/2 f'(x)= f'(x)= f'(x)= : C) f(x)= 3/4x2/3 +5/6x3/2 + 3/4x3/2 f'(x)= f'(x)= f'(x)= Happy Calculating!!!